Особенности внедрения технократической модели информационной демократии в странах мира - Митко, Антоніна Миколаївна; Mytko, Antonina M. (Wyższa Szkoła Informatyki i Ekonomii Towarzystwa Wiedzy Powszechnej w Olsztynie, 2015)
В статье поднимается проблема того, что ключевым в современной теории демократии должен стать вопрос о том, как с помощью современных информационно-коммуникационных технологий привлечь большинство граждан к решению политических проблем. Акцентировано внимание на мировом опыте, который предоставляет несколько моделей и механизмов внедрения и реализации информационной демократии, основанные, в первую очередь, на нормативно-правовой базе, состоящей из законодательства международного, национального и локального уровней. В процессе внедрения информационной демократии можно выделить несколько тенденций, как: рост роль СМИ, а особенно сети Интернет, для разнообразия форм политического участия граждан в политических процессах и выражения общественного мнения относительно событий в политической системе государства. Проанализировано, к каким результатам приведет внедрение технократической модели информационной демократии.

The article analyses the assertion in how far the main approach to a modern theory of democracy may be primarily result from a successful and attractive implementation of mod¬ern information and communication technologies to encourage the majority of a given popula¬tion to an active participation in political problem solutions. The attention is focused on global experience, which provides several models and mechanisms for the introduction and implemen¬tation of information democracy, based primarily on the legal framework, the latter consisting of international law and the compliance with national and local jurisdiction. In the process of implementation of information democracy several trends are of key importance. Ranking first is media-growth, foremost the expansion and general accessibility of the Internet, which encour¬ages various forms of the citizens' active participation in the political process and facilitates the expression of public opinion regarding the events in the country's political system. The author presents an analysis of the reasonably possible outcomes resulting from a successful implemen¬tation of a technocratic model of information democracy.
Features of the implementation of a global technocratic model of information democracy
Keywords: технократическая модель; информационно-коммуникационные технологии; электронное правительство; информационная демократия; законы; technocratic model; information democracy; e-government; laws; information and communication technologies